ANALISIS PENGENDALIAN INTERNAL SISTEM PENGGAJIAN MENGGUNAKAN PENDEKATAN COSO PADA CV XYZ - Fajarsari, Ike Meilani; Dini, Maya (Universitas YPPI Rembang, 2022)
Employees are human resources (HR) that are very important in a company. In realizing the mission and vision of a company, the company can utilize its human resources as optimally as possible, in order to provide added value for the company. Problems regarding the payroll system also occur in CV XYZ, the payroll internal control system is still not controlled. Preventive efforts in the evaluation process prevent fraud by developing an internal control system with COSO. The research method used is descriptive qualitative method. Collecting data by interview and collection of documentation. Internal control using COSO includes the control environment, risk assessment, control activities, information and communication, and monitoring. We recommend that COSO control can be applied to the company, it aims as a company evaluation of the employee payroll system that has an impact on employee productivity.Keywords: COSO, payroll system, employees, internal control.